PENGEMBANGAN MEDIA VIDEO MOTION GRAPHIC DALAM PEMBELAJARAN MENULIS PANTUN PADA MASA PANDEMI COVID 19 - Solihatini, Imas Tintin; Abidin, Yunus; Aljamaliah, S. Nailul Muna (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The main objective of the research is to design and develop motion graphic video media in learning to write rhymes. The research method used is design and development (D&D) and the ADDIE development model. This study concludes that based on the assessment of media experts, the developed media shows a percentage of 88% with a very decent category. The assessment of the material expert shows a percentage of 71.2% with a decent category. Based on user ratings, namely teachers and students, the media developed was categorized as very feasible based on the teacher's view and received an assessment in the very appropriate category based on the responses of students. This shows that motion graphic video media can be used as a medium for learning to write poem.